A Critical Criminological Study of Destructive Fishing Crimes in The Serutbar Conservation Area - Charly Timothy Hahury; Yanti Amelia Lewerissa; J.E. Latupeirissa (Asian Journal of Social and Humanities, 2026)
Maluku Province, as one of the archipelagos with the greatest potential for marine resources in Indonesia, is vulnerable to the threat of maritime crime, particularly destructive fishing practices (the use of fish bombs and poison), including those occurring in the Serutbar Conservation Area. This study aims to analyze destructive fishing crimes in the Serutbar Conservation Area not only as a phenomenon of individual deviance (fishermen) but also as a form of structural and ecological injustice. Using a critical criminology approach, this study examines criminogenic factors such as structural poverty, the marginalization of traditional fishermen, the power relations between financiers (cukong) and perpetrators in the field, and the suboptimal effectiveness of current positive law in prosecuting intellectual actors. The results of the study indicate that destructive fishing practices in the Serutbar Conservation Area are rooted in the economic pressures of coastal communities caused by limited fishing space and lack of access to environmentally friendly technology, which are then exploited by organized crime syndicates. From a critical criminology perspective, repressive law enforcement that targets only the main perpetrators (small-scale fishermen) has proven ineffective in providing a deterrent effect and ignores the massive damage to the ecosystem. Therefore, a reconstruction of criminal law policy is needed that combines prevention, criminalization of corporate intellectual actors, and a restorative justice approach that focuses on environmental restoration and alternative economic empowerment for coastal communities in Maluku, particularly those living around the Serutbar Conservation Area.